Interventions for the control of Crimean-Congo hemorrhagic fever and tick vectors - de la Fuente, José; Ghosh, Srikant; Lempereur, Laetitia; Garrison, Aura; Sprong, Hein; Lopez-Camacho, Cesar; Maritz-Olivier, Christine; Contreras, Marinela; Moraga-Fernández, Alberto; Bente, Dennis A. (npj vaccines, 2024)
Crimean-Congo hemorrhagic fever (CCHF) is a zoonotic disease associated with its principal tick vector, Hyalomma spp. with increasing fatal incidence worldwide. Accordingly, CCHF is a World Health Organization-prioritized disease with the absence of effective preventive interventions and approved vaccines or effective treatments. This perspective raised from a multidisciplinary gap analysis considering a One Health approach beneficial for human and animal health and the environment exploring international collaborations, gaps and recommendations.